Tuberculosis in the AIDS era. - Sepkowitz, K A (1995)
A resurgence of tuberculosis has occurred in recent years in the United States and abroad. Deteriorating public health services, increasing numbers of immigrants from countries of endemicity, and coinfection with the human immunodeficiency virus (HIV) have contributed to the rise in the number of cases diagnosed in the United States. Outbreaks of resistant tuberculosis, which responds poorly to therapy, have occurred in hospitals and other settings, affecting patients and health care workers. This review covers the pathogenesis, epidemiology, clinical presentation, laboratory diagnosis, and treatment of Mycobacterium tuberculosis infection and disease. In addition, public health and hospital infection control strategies are detailed. Newer approaches to epidemiologic investigation, including use of restriction fragment length polymorphism analysis, are discussed. Detailed consideration of the interaction between HIV infection and tuberculosis is given. We also review the latest techniques in laboratory evaluation, including the radiometric culture system, DNA probes, and PCR. Current recommendations for therapy of tuberculosis, including multidrug-resistant tuberculosis, are given. Finally, the special problem of prophylaxis of persons exposed to multidrug-resistant tuberculosis is considered.